Search for Supersymmetry through the 3-lepton and large missing transverse momentum process with the ATLAS detector at CERN - Κουρκουμέλη-Χαραλαμπίδη, Αθηνά (2017)
Η διατριβή αυτή ανήκει στο χώρο της σωματιδιακής φυσικής